Aviation Security Law - Abeyratne, Ruwantissa. author. aut Link
XII, 287 p.
Keywords: The law plays a significant role in ensuring aviation security. This book addresses new and emerging threats to civil aviation; evaluates security tools now in use such as the Public Key Directory, Advance Passenger Information, Passenger Name Record and Machine Readable travel documents in the context of their legal and regulatory background; and discusses applicable security treaties while providing an insight into the process of the security audits conducted by the International Civil Aviation Organization (ICAO). The book also examines issues of legal responsibility of States and individuals for terrorist acts of third parties against civil aviation and discusses from a legal perspective the latest liability Conventions adopted at ICAO. The Conclusion of the book provides an insight into the application oflegal principles through risk management.